PSYCHOLOGICAL FEATURES OF THE EMOTIONAL SPHERE AND COPING STRATEGIES AT AGING - Novikova, Zhanna (PSYCHOLOGICAL JOURNAL, 2019)
The article analyzes theoretically elderly people’s emotional sphere, the internal and external factors, leading to strong negative emotions and lower emotional durability, and the factors leading to strong negative emotional states and, at the result, to the emotional aging. Elderly people can resist o aging, psychological, social and physical problems, if they have formed psychological maturity and high volitional qualities.The article specifies that elderly people are characterized by negative emotions, negative attitudes to their life, and pessimistic mood, and also they do not have a vision of their future prospects. However, it is noteworthy that aging is different for different people and it can be of the convergent type, as well as of divergent type, and these types have different options.The following methods were used for the empirical study: Self-Assessment of Psychological States (according to G. Eysenck); “Copying Strategies” questionnaire developed by R. Lazarus, S. Folikman, and adapted by T. L. Kryukova, E. V. Kuflyak, M. S. Zamshelova.This empirical study was done in two stages, the first stage was in 2011, and the second one was in 2018. The empirical study aim was to determine specifics of elderly people’s emotional states and the coping strategies used actively by them. The comparative analysis of the data from two groups was performed.The following results were obtained during the study analysis: such emotional states as anxiety, frustration, and rigidity prevail at elderly people, but aggressive behavioural patterns are not used by elderly people. Elderly people show passive behaviour: distance and social support, but also active behaviour: self-control, acceptance of responsibility and positive reassessment in their behavioural repertoire. The results of two groups were compared with the help of the statistic analysis, and it shows that the data of the groups are not different statistically. But, an important change in elderly people’s emotional states and coping-strategies has been identified. The indicators of anxiety, frustration and rigidity have stayed on the high level, but the indicators of such coping strategies as “distance”, “social support” have risen, and the indicator of “avoidance” has become lower.The next research task is to determine factors contributing to formation and fixation of negative emotional states and unproductive coping strategies of elderly people.